PTU-153 Diagnosis of coeliac disease among children whose mothers have coeliac disease: a united kingdom general population-based cohort. (22nd June 2015) - Tata, LJ; Zingone, F; Fleming, KM; Card, TR; Crooks, C; Ciacci, C; West, J
Abstract : Introduction: Our aim was to quantify the risk of clinically diagnosed coeliac disease (CD) in children of mothers with coeliac disease to assess this burden in the general population of the United Kingdom. Method: We used a large population-based general practice database (The Health Improvement Network) to obtain data pertaining to all children born between 1990 and 2010 registered with general practices whose records were linked to their mothers' medical records. We identified all mothers and children diagnosed with CD and assessed the maternal-child CD association using logistic regression with generalised estimating equation modelling, adjusting for potential confounders. Results: There were 708 children diagnosed with CD in the study population of 798, 343 children up to 16 years of age. Among children with CD, 10.3% had mothers who also had CD whereas maternal CD diagnoses were 0.3% among the children without CD. This equated to offspring CD risks of 3.2% vs. 0.1% among mothers with CD versus those without. The odds ratio for offspring CD associated with maternal CD was 36.7, 95% confidence interval 28.2–47.7 after adjusting for child sex, socioeconomic deprivation, year of birth, Caesarean delivery, and maternal age. Conclusion: A child born to a woman with CD is almost 40 times more likely to be diagnosed with CD than if the mother does not have CD. In absolute terms, 3.1% more children will receive a diagnosis, considerably raised from the average population risk. This could be due to genetics, shared environmental risk factors within families or ascertainment bias. Disclosure of interest: None Declared.